The quality of accounting information in light of the impact of the use of cloud computing: An exploratory study of the opinions of a sample of academics and professionals in Iraq - Machi, Ahmed Hssein; Al-Juaifari, Murtadha Saleh Mahdi; Abdulzahra, Ali Noori (Journal of Economic, Administrative and Legal Sciences, 2023)
The research aims to clarify the impact of cloud computing on the financial performance of Iraqi companies، improve the quality of accounting information and financial reports، and indicate the benefits and actions to be taken to improve their adoption policies through the use of a questionnaire to analyze the research variables and to show the impact and correlation using a set of appropriate statistical methods using the statistical program (SPSS)، and the researchers reached a set of conclusions، the most important of which are: There is a strong statistically significant correlation between cloud computing and the quality of accounting information. Also، there is a statistically significant impact relationship between cloud computing and the quality of accounting information. The need to encourage Iraqi companies to use cloud accounting applications in companies listed in the Iraqi Stock Exchange، which leads to improving their performance and the quality of their information and financial reports. And it reached a set of recommendations، the most important of which is the need to provide high-quality data centers to motivate companies to invest in cloud accounting. All accountants receive training in the field of technology and develop their technological skills.